2012
DOI: 10.1007/s12008-012-0158-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving MTM-UAS to predetermine automotive maintenance times

Abstract: The preventive knowledge of serviceability times is a critical factor for the quantification of after-sales services costs of a vehicle. Predetermined motion time system are frequently used to set labor rates in industry by quantifying the amount of time required to perform specific tasks. The first such system is known as Methods-time measurement (MTM). Several variants of MTM have been developed differing from each other on their level of focus. Among them MTM-UAS is suitable for processes that average aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…Gironimo vd. [9], MZÖ-UAS yönteminin ergonomik faktörleri dikkate almamasından kaynaklanan sıkıntıları gidermek için iyileştirme önerileri sunmuşlardır. Bures ve Pivodova [10], MZÖ-1 yöntemini iş ölçüm yöntemlerinden olan REFA ve BasicMOST yöntemleri ile karşılaştırmışlardır.…”
Section: Metot Zaman öLçümü (Mzö) Yöntemi̇ (Methods Time Measurement (Munclassified
“…Gironimo vd. [9], MZÖ-UAS yönteminin ergonomik faktörleri dikkate almamasından kaynaklanan sıkıntıları gidermek için iyileştirme önerileri sunmuşlardır. Bures ve Pivodova [10], MZÖ-1 yöntemini iş ölçüm yöntemlerinden olan REFA ve BasicMOST yöntemleri ile karşılaştırmışlardır.…”
Section: Metot Zaman öLçümü (Mzö) Yöntemi̇ (Methods Time Measurement (Munclassified
“…The latter is based on long-term workability and employability, which represent key elements in ergonomics and human factors. Ergonomics has ancient roots in the age of ancient Egypt and the Greek and Roman period [39]; in more recent times, research studies have shown the positive effects of applying ergonomic principles to manufacturing, e.g., in workplace design [40,41]. In [42], a study was described to demonstrate how the application of ergonomic principles during product design can effectively reduce life cycle costs.…”
Section: Human Factors In Sustainable Manufacturingmentioning
confidence: 99%
“…In particular, 3D digital simulation was employed to calculate two ergonomic indices, namely the Posture Evaluation Index-PEI, and the Work Cell Evaluation Index-WEI, defined in [40], making it possible to numerically assess the ergonomic postures so that critical configurations can be identified and optimized through a proper layout reconfiguration. The Posture Evaluation Index allows us to identify whether a specific posture is deemed critical or not by integrating the results of the Low Back Compression Analysis (LBA) [46], Rapid Upper Limb Assessment (RULA) [47], and Ovako Working Posture Analysis System (OWAS) [48] in a synthetic adimensional index able to evaluate the "quality" of a posture, according to the equation presented in [40]:…”
Section: Definition Of the Ergonomics Indicesmentioning
confidence: 99%
“…For the evaluation of the interaction with people, the use of manikins is necessary. Recent studies have shown some advantages of using manikins in a virtual environment and for the simulation of human tasks (Di Gironimo et al, 2012a;Di Gironimo et al, 2012d).…”
Section: Ergonomic Analysis and Evaluation Of Concept Characteristicsmentioning
confidence: 99%